Life stories: Unraveling the academic configuration of a multifaceted and multidisciplinary field of knowledge - López-Montero, Rocío; García-Navarro, Carmen; Delgado-Baena, Antonio; Vela-Jiménez, Rocío; Sianes, Antonio (Frontiers in Psychology, 2022)
In the field of qualitative research, life stories are consolidated as one of the most important techniques within the biographical method. However, due to the multiplicity of techniques covered by this method, as well as the different disciplines within which it is applied, its contributions and scope do not present a clear delimitation. This article aims to clarify the field of knowledge generated through life stories, applying bibliometric analysis to a body of 2670 articles indexed in the Web of Science. The publication patterns obtained from this database reflect how the knowledge transferred from psychology occupies a central place, leaving a blurred position to that produced from sociology or anthropology. In this sense, it is essential to open new lines of research that allow us to know the differences between different techniques and disciplines when applying this methodology.